2022
DOI: 10.1002/advs.202206180
|View full text |Cite
|
Sign up to set email alerts
|

High‐Rate Alkaline Water Electrolysis at Industrially Relevant Conditions Enabled by Superaerophobic Electrode Assembly

Abstract: Alkaline water electrolysis (AWE) is among the most developed technologiesfor green hydrogen generation. Despite the tremendous achievements in boosting the catalytic activity of the electrode, the operating current density of modern water electrolyzers is yet much lower than the emerging approaches such as the proton-exchange membrane water electrolysis (PEMWE). One of the dominant hindering factors is the high overpotentials induced by the gas bubbles. Herein, the bubble dynamics via creating the superaeroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…S2 †). FeP-CoP was selected as the constituent since it demonstrated excellent OER activity as documented in our previous work, 25,26 and we envisage that the phosphide domains might enable the transfer of oxidation sites at high anodic potentials from carbon to the phosphide surface. The mechanical mixing of phosphide and carbon minimized the length of the interface where the catalytic oxidation of carbon might proceed.…”
Section: Mechanically Mixed Composite Electrodementioning
confidence: 99%
“…S2 †). FeP-CoP was selected as the constituent since it demonstrated excellent OER activity as documented in our previous work, 25,26 and we envisage that the phosphide domains might enable the transfer of oxidation sites at high anodic potentials from carbon to the phosphide surface. The mechanical mixing of phosphide and carbon minimized the length of the interface where the catalytic oxidation of carbon might proceed.…”
Section: Mechanically Mixed Composite Electrodementioning
confidence: 99%
“…[60] Although this approach can address the effects of bubble retention to some extent, bubbles can still generate a "gas blanket" between the electrode and the diaphragm and may cause complicated local convection of the electrolyte, which causes additional overpotential losses. [61][62][63] Shen et al used a 3D computational fluid dynamics model to study the transient bubble behavior in a commercial AWE. They found that bubbles would form bubble plugs within the flow channel, which had a significant negative impact on the electrolyzer's performance.…”
Section: Bubble Effect On the Surfacementioning
confidence: 99%
“…Alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEMWE), and anion exchange membrane water electrolysis (AEMWE) are the three types of WE procedures based on the electrolyte employed [ 10 , 11 , 12 ]. AWE is a technique that uses alkaline solutions as electrolytes to electrolyze water to produce hydrogen and oxygen.…”
Section: Introductionmentioning
confidence: 99%